A comprehensive meta-analysis of the self-serving bias in schizophrenia spectrum disorders compared to non-clinical subjects. (January 2021) - Müller, Hendrik; Betz, Linda T.; Bechdolf, Andreas
Highlights: Comprehensive meta-analysis of self-serving bias in schizophrenia spectrum disorders. Greater self-serving bias in schizophrenia spectrum disorders than in controls. Self-serving bias seems specific to persecutory delusions and paranoid ideation. The effect is a function of the method of measurement and cultural background. Self-esteem, depression, and jump to conclusion bias are influencing factors. Abstract: We conducted a comprehensive meta-analysis to investigate the self-serving bias SSB in schizophrenia spectrum disorders (SSD) to examine its specificity for persecutory delusions, paranoia, and to explore sources of heterogeneity in previous findings. We included 56 studies with n = 2501 patients with SSD and n = 2601 non-clinical controls in the main random-effects model using Hedges' g . Data quality and risk of bias were assessed. Results showed that SSB was a function of the method of measurement, and the cultural background of the participants, thereby identifying important sources of heterogeneity in measuring SSB in patients with SSD. The SSD group was somewhat more prone to SSB ( g  = 0.17), especially, when in a state of active persecutory delusion ( g  = 0.32/0.57), when they scored high in paranoid ideation ( r  = 0.25), or tended to jump to conclusions ( r  = 0.43). High self-esteem in the SSD group was associated with high SSB ( r  = 0.34); depression with low SSB ( r =-0.39).